2015
DOI: 10.1016/j.simyco.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Resolving thePhomaenigma

Abstract: The Didymellaceae was established in 2009 to accommodate Ascochyta, Didymella and Phoma, as well as several related phoma-like genera. The family contains numerous plant pathogenic, saprobic and endophytic species associated with a wide range of hosts. Ascochyta and Phoma are morphologically difficult to distinguish, and species from both genera have in the past been linked to Didymella sexual morphs. The aim of the present study was to clarify the generic delimitation in Didymellaceae by combing multi-locus p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
340
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 319 publications
(406 citation statements)
references
References 62 publications
11
340
0
7
Order By: Relevance
“…Currently, Phoma sensu stricto is included in the family Didymellaceae, and the other Phoma-like fungi belong to other phylogenetic families, i.e., Cucurbitariaceae, Leptosphaeriaceae, Phaeosphaeriaceae, etc. (39,40,42,43). It is of note that one of the frequently isolated species in our study, Didymella heteroderae (5.2% of isolation frequency), has never been mentioned as an etiologic agent of human infections even though our results reveal its ability to grow and to sporulate at 37°C, which is uncommon in that genus and suggests its potential pathogenicity.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Currently, Phoma sensu stricto is included in the family Didymellaceae, and the other Phoma-like fungi belong to other phylogenetic families, i.e., Cucurbitariaceae, Leptosphaeriaceae, Phaeosphaeriaceae, etc. (39,40,42,43). It is of note that one of the frequently isolated species in our study, Didymella heteroderae (5.2% of isolation frequency), has never been mentioned as an etiologic agent of human infections even though our results reveal its ability to grow and to sporulate at 37°C, which is uncommon in that genus and suggests its potential pathogenicity.…”
Section: Discussionmentioning
confidence: 48%
“…Both cases are from immunocompromised patients; in one case P. cyclothyrioides caused skin lesions of the lower extremities, and in the second case it produced a systemic coinfection together with Phaeoacremonium parasiticum (37,38). Even though Phoma sporulates easily, it is commonly misidentified as other related genera, such as Ascochyta, because the genera have similar morphologies, physiologies, and nucleotide sequences (39,40). Boerema et al carried out one of the most comprehensive revisions of the taxonomy of the genus Phoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hashimoto et al (2017) introduced Hermatomycetaceae to place this genus. Chen et al (2015) introduced this coelomycetous genus and phylogenetic analyses showed that it belongs in Didymellaceae.…”
Section: Catenulomyces Egidi and De Hoogmentioning
confidence: 99%
“…Chen & L. Cai Chen et al (2015) introduced this genus with a coelomycetous asexual morph and DNA sequence analyses showed that it belongs in Didymellaceae.…”
Section: Catenulomyces Egidi and De Hoogmentioning
confidence: 99%
See 1 more Smart Citation